New E-miyabenol isomer isolated from grapevine cane using centrifugal partition chromatography guided by mass spectrometry. Issue 20 (20th May 2015) - Papastamoulis, Yorgos; Bisson, Jonathan; Temsamani, Hamza; Richard, Tristan; Marchal, Axel; Mérillon, Jean-Michel; Waffo-Téguo, Pierre
Abstract: Stilbenoids have received increasing attention over the last two decades since the discovery of resveratrol in wine. With an ever-growing rhythm, a multitude of biological activities of naturally occurring stilbenes are being reported. In this work, we investigated minor stilbenoid compounds from Vitis vinifera stalks. The compounds were purified by means of centrifugal partition chromatography (CPC), a countercurrent-separation technique. Electrospray ionization–ion trap mass spectrometry (ESI–IT-MS) after optimization proved to be extremely efficient for the detection of these new molecules, providing both structural information for structure elucidation and a means to achieve identification even with minute amounts. Here a new stereoisomer of E -miyabenol C, E - cis - cis -miyabenol C (2 ), along with the already reported E - trans - cis -miyabenol C (1 ) and E - cis - trans -miyabenol C (3 ), was purified from a complex Vitis vinifera cane extract, using adapted solvent systems K and L from the 'Arizona' solvent system range, without the need for any solid support. Moreover, compounds 1 –3 showed an inhibitory activity on α-synuclein filament formation. Graphical abstract: